THE CONSTRUCTION OF BRAZILIAN NATIONAL IDENTITY AND THE ROLE OF EDUCATION IN THE INDIGENOUS “CIVILIZATION” PROCESS IN CAPITALIST SOCIETY - Paula Alves Nascimento, Anna (Revista Gênero e Interdisciplinaridade, 2025)
The present text aims to discuss the construction of Brazilian national identity and how this process impacted indigenous communities through the so-called 'civilizing process.' In this context, during the 19th century, the role of education stands out, especially the actions of the Capuchin order among indigenous populations, as part of the efforts of the State and the Church to integrate the native peoples into the logic of capitalist society.